Direct Effect of Chenodeoxycholic Acid on Differentiation of Mouse Embryonic Stem Cells Cultured under Feeder-Free Culture Conditions. (29th December 2012) - Park, Soon-Jung; Lee, Seul-Bi; Lee, Dong-Sup; Ryu, Young-Joon; Lee, Gene; Cho, Jaejin
Abstract : Chenodeoxycholic acid (CDCA), a farnesoid X receptor (FXR) ligand, is a member of the nuclear receptor family and is probably involved in regulating the cellular activities of embryonic stem (ES) cells. Recently, although it was reported that the FXR ligand can mediate differentiation, apoptosis, and/or growth arrest in several cell types, it is still not well known how CDCA mediates effects in ES cells. Therefore, we investigated the direct effect of CDCA on mES cells. Feeder-free mES cells were treated in a dose-dependent manner with CDCA (50, 100, and 200  μ M) for 72 h, and then a 100  μ M CDCA treatment was performed for an additional 72 h. We analyzed the morphology, cell growth, cell characteristics, immunocytochemistry, and RT-PCR. In CDCA-treated cells, we observed the disappearance of pluripotent stem cell markers including alkaline phosphatase, Oct4, and Nanog and a time- and dose-dependent increase in expression of nestin, PAX6, and α -smooth muscle actin, but not α -fetoprotein. The 100  μ M CDCA-treated cells in their second passage continued this differentiation pattern similar to those in the controls. In conclusion, these results suggest that CDCA can guide mES cells by an FXR-independent pathway to differentiate into ectoderm and/or mesoderm, but not endoderm.